Corpo : este é o meu céu : acontecimento e lugar da morte - Cardoso, Nelson Manuel Ferreira, 1974- (2014)
Ontological death is the subject matter of this research, because death is the ultimate event of the body. This one is terminated, at the same time, with the being (place of love on earth). It is not enough to say I’m the place occupied by me: the individual is born a kinetic place because evolves over space. After the end and subsequently fall of the being on horizontal plan, non being occupies the inert place. He will stay memory on earth, even after watering down – it will be a symbolic place. Death is a visibility process, started somewhere inside body, but showing itself outside epidermis. Death is an image: but what kind of death image to be represented, between dead body seen before, and not being anymore? Grave is architectural place, negative, that transforms and solves corpse far away from sight. Death is a priori status changing, non existence or energy moving to other living beings. If there is metaphysical existence beyond nothing, believer judges about